Why do ammonium salt/phenol-based deep eutectic solvents show low viscosity? - Chen Fan (Elsevier, 2022)
The viscosity of deep eutectic solvents (DESs) plays an important role in determining how they are used industrially. In order to gain a deeper insight into the parameters which affect the viscosity of ionic DES, a series of systems composed of ammonium salts and two types of representative donors were prepared and characterized. They were investigated by quantum-chemistry calculations and molecular dynamics simulations. The viscosity of phenol/4-methylphenol-based system is much lower than that of glycolic acid-based system. Moreover, DESs containing glycolic acid exhibit higher activation energy values compared with DESs containing phenolics. It was found the existence of a strong charge transfer complex between glycolic acid and ammonium salt, thus suggesting its vital role in the fluidity difference of studied mixtures. The hydrogen bonds of glycolic acid-based system are partially covalent and partially electrostatic, manifested via atoms in molecules (AIM) analysis. Additionally, Cl−⋯HOphenolic hydroxyl is expected to be less covalent than Cl−⋯HOcarboxyl, which is also identified by lower delocalization index in the AIM basin. The interaction network stability of glycolic acid-based DES is more robust than that of phenolics-based one due to the strong covalency of hydrogen bond. This is the main reason that ammonium salt/phenol-based DESs show low viscosity. This work gives new perspectives on more rational design of novel DES with low viscosity.